Characterization of Lipolytic Activity from Nyamplung (Calophyllum inophyllum L.) Seeds - Lalu Rudyat Telly Savalas; Mukhtar Haris; Eka Junaidi; Saprizal Hadisaputra; Yunita Arian Sani Anwar; Lalu Anugrah Dimas Juniarly (Study Program of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Pakuan, 2026)
Lipases are biocatalysts widely utilized in industrial and biotechnological processes due to their ability to catalyze the hydrolysis and synthesis of ester bonds. The search for novel lipase sources from plant materials continues to attract attention, particularly for sustainable and eco-friendly enzyme production. This study aims to isolate and characterize lipase from Nyamplung (Calophyllum inophyllum L.) seeds. The enzyme was extracted from germinated seeds and subjected to activity assays under varying temperature, pH, and germination length conditions. The highest lipase activity was obtained at 35 °C and pH 7.5, with an activity of 0.92 U/mL. The maximum activity was observed after 15 days of imbibition, reaching 1.06 U/mL. Protein characterization through SDS-PAGE revealed multiple bands with molecular weights of 28, 21 and 19 kDa, indicating the presence of isoenzymes or subunit structures. These results suggest that Nyamplung seed lipase exhibits suitable catalytic properties for biotechnological applications. The enzyme’s moderate temperature and neutral pH optima make it a potential candidate for use in food and oleochemical industries.